Pengaruh Kedisiplinan Belajar terhadap Kemampuan Berpikir Kritis dalam Pembelajaran Matematika - Windana Jopan Marbun; Khoerunisa Khoerunisa; Khofipah Khofipah (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
The study aims to analyze the relationship between learning discipline and students' critical thinking abilities in math learning. A quantitative approach with correlational survey methods is used in this study. Sample of 44 junior high school students selected through simple random sampling technique. Instruments used as lamps to measure learning discipline and tests to measure critical thinking ability. Data analysis was performed through Liliefors normality testing, Pearson correlation testing, and simple linear regression. The normality test results show that discipline learning data is normally distributed (Lo = 0.0995 < Ltable = 0.133), whereas critical thinking data is not normally distributed (Lo = 0.2266 > Ltable = 0.133). The correlation test results show the value of r = 0.211 and thitung = 1.423 < ttable = 1.683, meaning there is no significant relationship between learning discipline and critical thinking ability. The regression results also show the value of Fhitung = 2.15 < Ftabel = 4.08, which means there is no significant influence between learning discipline on critical thinking ability. Thus, that learning discipline does not affect significantly on students' critical thinking ability in math learning. This results in a more comprehensive learning approach to develop critical thinking skills.